2014
DOI: 10.3892/br.2014.373
|View full text |Cite
|
Sign up to set email alerts
|

Expression signature of microRNA-155 in hepatitis C virus genotype 4 infection

Abstract: Hepatits C virus (HCV) genotype 4 (GT4) shows low treatment response rates and discrepancies when compared to other genotypes. However, the reason underlying these discrepancies remains unclear due to the limited number of studies on GT4. microRNA-155 () is a noteworthy example of a discrepancy in GT4, as it was found to be upregulated in genotypes 1, 2 and 3 HCV infection, but downregulated in GT4-HCV-infected peripheral blood mononuclear cells (PBMCs). The present study aimed to investigate the expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 22 publications
(31 reference statements)
3
8
0
Order By: Relevance
“…The tumor suppressor miRNA miR‐15a, which is usually down regulated or deleted in prostate cancer found to be overexpressed in liver tissue of HCC patients but again we failed to correlate the expression level of this miRNA in plasma. Such incongruities in miRNA expression patterns between serum and tissue have been reported previously, which again supported that circulating miRNAs might not always be shed from diseased organ. Recently, Tewari group has also documented that among 79 circulating miRNAs identified so far as biomarkers of different solid tumors, 47 circulating miRNAs are over expressed in hematological cells .…”
Section: Discussionsupporting
confidence: 84%
“…The tumor suppressor miRNA miR‐15a, which is usually down regulated or deleted in prostate cancer found to be overexpressed in liver tissue of HCC patients but again we failed to correlate the expression level of this miRNA in plasma. Such incongruities in miRNA expression patterns between serum and tissue have been reported previously, which again supported that circulating miRNAs might not always be shed from diseased organ. Recently, Tewari group has also documented that among 79 circulating miRNAs identified so far as biomarkers of different solid tumors, 47 circulating miRNAs are over expressed in hematological cells .…”
Section: Discussionsupporting
confidence: 84%
“…miR‐155 has a critical prognostic role in HCV infection, leukemia, and lymphomas . miR‐155 expression is one of the discrepancies in HCV genotype 4 infections, as it does not vary in polymorph nuclear cells (PMNCs) compared to healthy controls, unlike its expression in HCV genotypes 1, 2, and 3 infections . The different expression of miR‐155 may affect the prognosis and may explain the resistance to the treatment pattern of HCV genotype 4 .…”
Section: Introductionmentioning
confidence: 99%
“…miR‐155 expression is one of the discrepancies in HCV genotype 4 infections, as it does not vary in polymorph nuclear cells (PMNCs) compared to healthy controls, unlike its expression in HCV genotypes 1, 2, and 3 infections . The different expression of miR‐155 may affect the prognosis and may explain the resistance to the treatment pattern of HCV genotype 4 . On the other hand, studies that investigated the role of miR‐155 in CML and AML demonstrated that it is upregulated in cells and circulating exosomes .…”
Section: Introductionmentioning
confidence: 99%
“…Over-expression of miR-155 was found to strengthen defenses against viruses by counteracting the immunosuppressive effect of IL-10 or TGF-b on TLR3-induced antiviral activity [27]. However, a down-regulation of miR-155 has been reported in PBMCs infected with genotype 4 (GT4) but not GT1, 2 or 3 HCV [28]. Therefore, miR-155 appears to respond in a genotype-specific way.…”
Section: Mir-155 and Hepatitis Virusesmentioning
confidence: 75%
“…Therefore, miR-155 appears to respond in a genotype-specific way. It was also found to be a satisfactory prognostic factor and predictor of response to treatment with pegylated interferon/ribavirin, enabling differentiation between naïve non-responders and naïve sustained virological responders during GT4-HCV infection [28]. El-Ekiaby et al [29] reported evidence about GT4-HCV infection impairing the induction of miR-146 and -155 by IFN-a when TLR7 is agonized, which promotes the release of IFN-a.…”
Section: Mir-155 and Hepatitis Virusesmentioning
confidence: 96%